Motion and Dynamic Responses Approach for WindFloat Structures under Marine Loads - Scurtu, I C; Gârleanu, D; Garleanu, G (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
This paper presents performed Ansys CFX numerical simulation on WindFloat structures. The model of WindFloat was designed according to real use dimensions in DesignModeller in open sea simulation approach. Inside paper content marine loads acting offshore structures are presented according ABS rules and hydrodynamic response presented as RAO function. Data collected in the JONSWAP North Sea Wave Observation Project combined with WindFloat RAO will determine structure dynamic response. The results demonstrate the accuracy of RAO function approach for specific WindFloat in Jonswap spectra. Published in Preprints.org. Technium Journal decided to publish file with EiC guidance. https://www.preprints.org/manuscript/201809.0546/v1 doi: 10.20944/preprints201809.0546.v1